Role of Campylobacter jejuni as a placental pathogen. Issue 2 (February 1992) - Denton, K J; Clarke, T
Abstract : Members of the genus Campylobacter are well recognised as enteric pathogens but have rarely been implicated as human placental pathogens. A case of septic abortion due to C jejuni is reported. This occurred in a previously healthy woman with a diarrhoeal illness. The presence of chorioamnionitis raises the possibility of ascending infection rather than septicaemic spread as the pathogenesis. Members of the genus Campylobacter have special culture requirements and their incidence as placental pathogens may therefore be underestimated.